THE EFFECT OF DECOMPOSITION TIME AND DOSE OF CHICKEN MANURE FERTILIZER ON GROWTH AND PRODUCT OF Asystasia gangetica (L.) subsp. Micrantha - E. C., Sembiring; Duarsa, M. A. P.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
The purpose of this research was to determine the effect of decomposition time and dose of chicken manure fertilizer on growth and product of Asystasia gangetica (L.) subsp. Micrantha. The research conducted at Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University on Jalan Raya Sesetan Gang Markisa. The research performed for 3 months by utilizing a completely randomized design (RAL) with factorial patterns method. The first factor was the decomposition time on 0 week (W0), 2 nd week (W2), and 4 th week (W4). The second factor was the quantity of chicken manure fertilizer with variable dose from 0 ton ha -1 (D0), 10 tons ha -1 (D10), 20 tons ha -1 (D20), and 30 tons ha -1 (D30).  There are in total 12 treatment combinations and each treatment was repeated for four times, hence total were 48 experimental units performed. The growth, yield, and plant growth characteristic were variables observed during this research. There was an interaction between decomposition time and dosage at all variables, with exception on the weight of dry leaves, total dry weight, and ratio between leaves & stem dry weight. The decomposition on 0 week showed result better than decomposition on 2 nd and 4 th week. The best dosage for Asystasia gangetica (L.) subsp. Micrantha growth & product was observed at 30 tons ha -1 . Based on above result, it is concluded that Asystasia gangetica (L.) subsp. Micrantha reacts the best during decomposition on week 0 with 30 ton ha -1 dosage.   Keywords: Asystasia gangetica, decomposition, results, Chicken Manure, growth